Моделирование и оценка погрешности способа измерения скорости ветра на высотах мезопаузы-нижней термосферы методом радиолокации метеорных следов по сигналам телевизионного вещания - Кукуш, В. Д.; Олейников, А. Н. (ХНУРЭ, 2011)
The possibility of using of terrestrial television broadcast signals as sounding signals for mesosphere-lower thermosphere (MLT, 80-105 km) wind measurements by the radio meteor method is investigated. The given work shows results of modelling and error estimation of the developed measuring technique.
Keywords: метод радиолокации метеорных следов; мониторинг ветровых движений; доплеровский сдвиг частоты